2008
DOI: 10.1063/1.2902295
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of electrically active interfacial layer defects which may cause threshold voltage instabilities in HfO2 based metal-oxide-silicon field-effect transistors

Abstract: Articles you may be interested inIdentification of the atomic-scale defects involved in the negative bias temperature instability in plasma-nitrided p -channel metal-oxide-silicon field-effect transistors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Ryan et al [15] have, as mentioned previously, also suggested a coupling between an oxygen deficient silicon and a hafnium atom in the interfacial layer. Ryan et al [15] have, as mentioned previously, also suggested a coupling between an oxygen deficient silicon and a hafnium atom in the interfacial layer.…”
Section: Inteface/near Interface Defects Generated In Bias Temperaturmentioning
confidence: 71%
See 3 more Smart Citations
“…Ryan et al [15] have, as mentioned previously, also suggested a coupling between an oxygen deficient silicon and a hafnium atom in the interfacial layer. Ryan et al [15] have, as mentioned previously, also suggested a coupling between an oxygen deficient silicon and a hafnium atom in the interfacial layer.…”
Section: Inteface/near Interface Defects Generated In Bias Temperaturmentioning
confidence: 71%
“…Ryan et al [15] also showed that the amplitude of these E' signals depends upon the position of the silicon/dielectric Fermi energy. This result demonstrates that the centers can act electronically as interface traps.…”
Section: Defects In the Interfacial Layermentioning
confidence: 96%
See 2 more Smart Citations
“…3 In SiO 2 , the difference is that the SILC due to neutral traps is stable, while the SILC from positive traps decays with increasing the relaxation time, for the reason that the trapped holes may detrap or recombine with electrons. [4][5][6] One of proposed SILC-related trap models in SiO 2 is the socalled E 0 center: OSi•, 7,8 in which the Si atom can capture or lose one electron and then becomes negatively and positively charged, respectively.…”
mentioning
confidence: 99%